2023
DOI: 10.1021/acs.inorgchem.3c04109
|View full text |Cite
|
Sign up to set email alerts
|

(Dis)Order and Luminescence in Silicon-Rich (Si,P)–N Network Sr5Si7P2N16:Eu2+

Marwin Dialer,
Monika M. Pointner,
Philipp Strobel
et al.

Abstract: In this work, we present the synthesis, characterization, and optical properties of Sr 5 Si 7 P 2 N 16 :Eu 2+ , the first tetrahedral (Si,P)−N network in which Si occupies more than 50% of the tetrahedra. While past studies have shown progress with anionic (Si,P)−N networks, the potential of silicon-rich compounds remains untapped. The synthesized compound Sr 5 Si 7 P 2 N 16 exhibits a unique mixture of substitutional order and positional disorder within its network. The analytical challenges posed by the simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…In this context, we also added new 31 P NMR data on literature known Sr 2 SiP 2 N 6 and Sr 5 Si 7 P 2 N 16 as reference for ordered (Si, P) networks. [7,8] LCC were used to confirm our results and provide insight into Sr 16 Si 9 P 9 O 7 N 33 where no NMR data were available. As an impetus for future research, we briefly investigated the optical properties of the SiPONs when doped with Eu 2 + .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this context, we also added new 31 P NMR data on literature known Sr 2 SiP 2 N 6 and Sr 5 Si 7 P 2 N 16 as reference for ordered (Si, P) networks. [7,8] LCC were used to confirm our results and provide insight into Sr 16 Si 9 P 9 O 7 N 33 where no NMR data were available. As an impetus for future research, we briefly investigated the optical properties of the SiPONs when doped with Eu 2 + .…”
Section: Discussionmentioning
confidence: 56%
“…Typically, total deviations below 3 % indicate a congruent model. [7] The comparison and evaluation of all five methods for the four compounds Sr 3 SiP 3 O 2 N 7 (1), Sr 5 Si 2 P 6 N 16 (2), Sr 5 Si 2 P 4 ON 12 (3), and Sr 16 Si 9 P 9 O 7 N 33 (4), are shown in Figure 5, where columns 1-5 represent each method, column 6 the total percentage deviation, rows 1-4 the respective compounds and the bottom row the reference data of pure nitridosilicates and nitridophosphates. Each cell shows a stack of all (Si, P) Wyckoff positions with their calculated values, their overall average, and their expected value.…”
Section: Low-cost Crystallographic Calculationsmentioning
confidence: 99%
“…By using a combination of analytical techniques, including single-crystal and powder X-ray diffraction as well as 31 P solid-state NMR and powder neutron diffraction, we were able to elucidate its complex network. After Sr 5 Si 7 P 2 N 16 , SrSi 2 PN 5 is the second silicon-rich, but this time, fully ordered (Si,P)–N network . The challenges posed by the chemical similarity and low X-ray contrast between the key elements were effectively addressed, highlighting the importance of methodological diversity in material characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Since the investigation and differentiation of these elements by X-ray diffraction are often considered insufficient, it must be complemented by other analytical methods. In a previous work, we have already proposed different approaches to distinguish Si 4+ and P 5+ , e.g., by exploiting their characteristic X-ray emissions in scanning transmission electron microscopy in combination with energy-dispersive X-ray spectroscopy at atomic resolution, better known as scanning transmission electron microscopy energy-dispersive X-ray (STEM-EDX) maps. , However, their discrimination is not limited to the interaction with their electron clouds, as we have shown by studying the 31 P solid-state NMR spectra of disordered oxonitridosilicate phosphates (SiPONs), Sr 3 SiP 3 O 2 N 7 and Sr 5 Si 2 P 4 ON 12 . While these methods provide reliable results, in this work, we were interested in further extending the analytical capabilities for this class of compounds by powder neutron diffraction (PND) and adding another method that interacts with the nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have previously shown that the elucidation of the structure and in particular the network in (Si, P) compounds is a multi-step process that often utilizes high-level analytics, such as atomic-scale scanning transmission electron microscopy (STEM). [7,8] However, we are interested in making this workflow more accessible by extending the analytical scope to more common methods, such as NMR. In this contribution, we present Sr 3 SiP 3 O 2 N 7 , Sr 5 Si 2 P 4 ON 12 and Sr 16 Si 9 P 9 O 7 N 33 as the first alkaline earth SiPONs.…”
Section: Introductionmentioning
confidence: 99%